Caribbean Report 10-03-1995 - Orr, Carol (anchor); Nuttall, Chris (correspondent); Ransome, Debbie (correspondent); Alleyne, Gary (correspondent); Julien, Kenneth (interviewee) (The British Broadcasting Corporation, 1995)
Cuban Foreign Minister Roberto Robaina has accused American Congressmen of plotting the mass extermination of the Cuban people. At the World Social Summit a dispute between the US and Cuba which had been delaying the approval of a final declaration on social development has been resolved. The final declaration is expected to be watered down in most areas in order to please the wide range of countries taking part in the Summit. Debbie Ransome looks at the commitment to concrete results from the Summit. France President Francois Mitterrand's last gesture of defiance against the US is to give full honors to Cuban President Fidel Castro when he visits. There are calls for Jamaica Opposition Leader, Edward Seaga to step down and take the role as Elder Statesman within the Jamaica Labour Party (JLP). An upsurge in American investments in Trinidad's energy industry seems to have stirred a revival in British interests in investing in the country. Jamaican sprinter Merlene Ottey won gold at the World Indoor Championships in Barcelona.
1. Headlines with Carol Orr (00:00-00:29)
2. Cuba accuses American Congressmen of plotting the mass extermination of the Cuban people (00:30-01:00)
3. A dispute which had been delaying the approval of a final declaration at the Social Summit has been resolved (01:01-04:34)
4. Debbie Ransome looks at the commitment to concrete results from the Social Summit (04:35-07:21)
Keywords: Cuba -- Foreign relations -- United States; United States -- Foreign relations -- Cuba; Embargo; Economic sanctions, American -- Cuba; Poverty -- International cooperation; Social planning; Economic assistance -- Developing countries; Debt relief -- Developing countries; France -- Foreign relations -- Cuba; Cuba -- Foreign relations -- France; Jamaica -- Politics and government; Politicians -- Jamaica; Leadership; Investments, Foreign -- Trinidad and Tobago; Investments, British -- Trinidad and Tobago; Energy industries -- Trinidad and Tobago; Trade missions; Athletes -- Jamaica; Track and field athletes -- Jamaica